Pengaruh Pengetahuan, Pelayanan, Sanksi, dan Kesadaran pada Kepatuhan Pajak Kendaraan Bermotor - Wahyu Putri Purwaningsih (Komunitas Dosen Indonesia, 2025)
Tax compliance on motor vehicles plays a crucial role in optimizing regional tax revenues, which directly contribute to local development and public welfare. Despite its importance, taxpayer compliance in Indonesia often faces challenges related to limited tax knowledge, inadequate service quality, inconsistent enforcement of tax sanctions, and low taxpayer awareness. These issues may reduce the effectiveness of regional tax collection, particularly for motor vehicle tax as one of the main sources of local revenue. This study aims to analyze the influence of tax knowledge, service quality, tax sanctions, and taxpayer awareness on the compliance of motor vehicle taxpayers at the SAMSAT Office in Rembang City. This research adopts a quantitative method with a descriptive approach. Data were collected using questionnaires distributed to 132 respondents selected through accidental sampling. The data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression with SPSS. The findings indicate that tax knowledge, service quality, tax sanctions, and taxpayer awareness positively influence motor vehicle taxpayer compliance, both partially and simultaneously. The study concludes that improving taxpayer literacy, enhancing service quality, applying sanctions consistently, and strengthening taxpayer awareness can significantly increase compliance. These results are expected to provide theoretical contributions to taxation studies and practical recommendations for local governments in formulating strategies to optimize tax revenues.